PENGARUH HARGA, CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PT. JNE CABANG MEDAN - Dita Amelia; Karina R; Nuel Simatupang; Bastian Jovial Sinuraya; Rahmat Rahmat (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2021)
The purpose of this research is to investigate the influence of price, brand image, service quality on customer satisfaction. The study was conducted at customers PT. JNE Cabang Medan. The type of research is explanatory research with quantitative approach. The population in the research were all customers of PT. JNE Cabang Medan. This research used 100 people as samples which chosen by purposive sampling and usde quesionnaire as data collection methods. The research also use descriptive statistical analysis and multiple regression analysis. The data is processed using the IBM SPSS (Statistical Product and Service Solutions) program version 25.0. Based on the results of the analysis, it is concluded that a significant influence between price, brand image and service quality on customer satisfaction partially and simultaneously.